Efficient Thesis Management: A Study of Universitas Multimedia Nusantara's Application Development Using Extreme Programming Principles - Cagananta, Cagananta; Istiono, Wirawan (Journal of Information Systems and Informatics, 2024)
The objective of this study is to develop and construct a thesis application utilizing the extreme programming approach, and to assess user contentment with the application using the End User Computing Satisfaction measurement technique. The Informatics study program at the Multimedia Nusantara University campus is encountering issues pertaining to the thesis procedure. The problems were identified through interviews with numerous lecturers, students, and the head of the Informatics department's study program at Universitas Multimedia Nusantara. The challenges include the decentralized distribution of information pertaining to theses, obstacles in obtaining thesis proposals, difficulties in obtaining details regarding the research specializations of lecturers, recapitulation of supervisors, and an array of additional issues. Based on these problems, a thesis application was designed and built using the extreme programming development method. The research findings indicate that the application has been effectively developed. The test results reveal that 87.267% of users strongly agreed that the application was highly beneficial in the thesis process.
Keywords: Extreme Programming; Information System; Thesis; Web Application